2014
DOI: 10.1186/1939-4551-7-25
|View full text |Cite
|
Sign up to set email alerts
|

ICON: chronic rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a public health problem that has a significant socio-economic impact. Moreover, the complexity of this disease due to its heterogeneous nature based on the underlying pathophysiology - leading to different disease variants - further complicates our understanding and directions for the most appropriate targeted treatment strategies. Several International/national guidelines/position papers and/or consensus documents are available that present the current knowledge and treatment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
189
1
21

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(216 citation statements)
references
References 344 publications
(401 reference statements)
5
189
1
21
Order By: Relevance
“…Investigators have nevertheless suggested a number of candidate genes associated with CRS, which has led to some interesting observations with intriguing implications. Reviews of genetics of CRS [615][616][617] have been presented elsewhere and identified genes are presented as a tabulated list (Table VII- 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have nevertheless suggested a number of candidate genes associated with CRS, which has led to some interesting observations with intriguing implications. Reviews of genetics of CRS [615][616][617] have been presented elsewhere and identified genes are presented as a tabulated list (Table VII- 10).…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom is nasal obstruction. 617 These symptoms are highly sensitive individually, but not specific. 655,656 Evidence has shown combining 2 or more symptoms together along with objective findings of disease (imaging, endoscopy) substantially increases diagnostic specificity and positive predictive value.…”
Section: Viid Crssnp: Diagnosismentioning
confidence: 99%
“…As a consequence a wide range of medical and surgical therapies have been used to treat CRS. (6)(7) researches evaluating the comparative efficiency of various treatments for chronic rhinosinusitis (CRS) is scanty.…”
Section: Introduction:-mentioning
confidence: 99%
“…[2] Chronic rhinosinusitis with NP is considered a more severe form of the disease with comorbid diseases and more frequent recurrences despite intensive medical and surgical treatment. [3] Fungi, bacteria, viruses, or their associated products may play a role in initiating or perpetuating abnormal and excessive mucosal inflammation. [4] The interaction between Staphylococcus aureus (S. aureus) and the sinonasal mucosa have been studied previously and invasion of the epithelium of the nasal mucosa by S. aureus has been identified by Sache et al [5,6] Whether the microorganism is located within the epithelial cells or not, S. aureus is capable of the formation of a T helper 2 (Th2) mediated cytokine pattern which leads to CRS with NP.…”
mentioning
confidence: 99%